2008
DOI: 10.3109/10929080801969725
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic navigation improves minimally invasive robot-assisted lung brachytherapy

Abstract: A modified integrated system for performing minimally invasive robot-assisted lung brachytherapy was developed that incorporated electromagnetic navigation and an improved robotic controller. The MIRA IV system performed significantly better than standard VATS and better than MIRA III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Most studies were found on computer-assisted bronchoscopy, where the bronchoscope can be navigated through the bronchial tree by localizing the tip and registering preoperative data, for example CT to patient [94]. Laparoscopic interventions such as lung brachytherapy [96] or Radio Frequency Ablation (RFA) [56] also have been performed. In the case of otolaryngologic (ENT) surgery, endoscopes have been localized using EM tracking to apply navigation under US/CT guidance [41,184].…”
Section: A Range Of Applicationmentioning
confidence: 99%
“…Most studies were found on computer-assisted bronchoscopy, where the bronchoscope can be navigated through the bronchial tree by localizing the tip and registering preoperative data, for example CT to patient [94]. Laparoscopic interventions such as lung brachytherapy [96] or Radio Frequency Ablation (RFA) [56] also have been performed. In the case of otolaryngologic (ENT) surgery, endoscopes have been localized using EM tracking to apply navigation under US/CT guidance [41,184].…”
Section: A Range Of Applicationmentioning
confidence: 99%
“…The system incorporates an experimental setup for accurate seed placement with commercially available dosimetry planning software. 5,6,[96][97][98][99] The dosimetry planning software incorporated into MIRA-V (upgraded MIRA robot) is a modified version of previously developed software for needle guidance in prostate brachytherapy. The end result is a complete system that allows planning and executing a brachytherapy procedure with increased accuracy.…”
Section: B13 Mira Robot-an Ultrasound Image-guided Lung Brachythementioning
confidence: 99%
“…The end result is a complete system that allows planning and executing a brachytherapy procedure with increased accuracy. 5 Two Automated Endoscopic Systems for Optimal Positioning (AE-SOP) arms are used to control the video camera and the instrument via voice control and the InterNAV3.0™ interface, respectively. These robotic arms are no longer commercially available.…”
Section: B13 Mira Robot-an Ultrasound Image-guided Lung Brachythementioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21]33 Studies have indicated that the quality of images captured by robot-assisted remote ultrasound systems correlate well with those captured by conventional ultrasound. [34][35][36] Robot technology has been reported for assistance in the diagnosis and treatment of lung diseases previously, [37][38][39] but the application of a 5G-based robot-assisted remote ultrasound system for use in lung disorders has not been reported to date. 5G networks have a high data transmission rate (peak rate up to 20 Gbps) and low network delay (approximately 1-10 ms).…”
Section: Discussionmentioning
confidence: 99%